English Language Teachers’ Perceptions on Knowing and Applying Contemporary Language Teaching Techniques (2017)
The aim of this study is to determine the perceptions of English language teachers teaching at a preparatory school in relation to their knowing and applying contemporary language teaching techniques in their lessons. An investigation was conducted of 21 English language teachers at a preparatory school in North Cyprus. The SPSS statistical package was used for the data analysis. Frequency and percentages were used to analyse the English language teachers’ knowledge, desire to learn, application of the innovative language techniques in their classrooms, experience of problems as well as teachers’ frequency of technique usage and where they learned these techniques. This study shows that the most known contemporary technique is communicative and less known contemporary language teaching techniques are blended/hybrid.